COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BEFORE AND DURING COVID-19 PANDEMIC - Surya, Kelly; Suhendah, Rousilita (International Journal of Application on Economics and Business, 2023)
Many industries around the world are impacted by COVID-19 pandemic. In this research, we aim to examine the impact of COVID-19 pandemic to firms’ financial performance by analyzing whether there is significant difference between firms’ profitability, liquidity, solvency, and activity before and during COVID-19 pandemic. This study uses purposive sampling method which resulted in 105 companies from food and beverages, telecommunication, transportation, tourism, restaurant, and hotel subsectors listed in Indonesia Stock Exchange from 2019 to 2020. We first divide the data into two period, 2019 for the period before COVID-19 pandemic and 2020 for the period during COVID-19 pandemic. Then, we uses paired samples t-test and Wilcoxon signedrank test for hypothesis testing. The data is processed using IBM SPSS Statistics 26. The results indicate that the profitability and activity of food and beverages companies differ significantly, while liquidity and solvency do not. The solvency of telecommunication companies differs significantly, while profitability, liquidity, and activity do not. The profitability, solvency, and activity of transportation companies differ significantly, while liquidity does not. The profitability, liquidity, solvency, and activity of tourism, restaurant, and hotel companies differ significantly.